1981
DOI: 10.1135/cccc19811523
|View full text |Cite
|
Sign up to set email alerts
|

Some derivatives of 4-aryl-2,3-dicyano-1-naphthol

Abstract: Reactions of vicinal aromatic dibromo derivatives Ia-d with the system copper(I) cyanide-tetramethylurea gave the vicinal dicyano derivatives IIa-d; products of partial substitution, Va-d, demethylation and deacetylation, IIIa-c, were also formed. The compounds IIIa-c were also prepared by direct demethylation of compounds IIa-c with the system anhydrous aluminium chloride-dichloroethane. The structures of selected compounds were determined by spectral methods. Compounds IIa-d have proved to have a moderate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Many other solvents have been used, for example, Me2SO,16,25,33,45 4-methylpyridine,89 nitrobenzene,17,70 dimethyl sulfone,71 acetonitrile,33 p-xylene,72 toluene,72 isopentyl alcohol,72 tetrahydrothiophene dioxide,71 W^V-dimethylacetamide,20,68,71 tetrahydrofuran (THF),33 and tetramethylurea (TMU). 25 Pyridine may have been chosen originally for its good solvent properties but was later found to form a complex with copper (I) cyanide and this has occasionally been preformed and used as a reactant. 19 Suzuki and Hanafusa14 demonstrated that for the replacement of one or more iodine atoms, HMPT acts as an efficient solvent (which may also have other roles) and this has been confirmed by other workers,26,33 although it is not invariably the best solvent.25 However, in view of its suspected carcinogenic effect,73 it should be used with care (see also section II).…”
Section: B Choice Of Solventmentioning
confidence: 99%
See 2 more Smart Citations
“…Many other solvents have been used, for example, Me2SO,16,25,33,45 4-methylpyridine,89 nitrobenzene,17,70 dimethyl sulfone,71 acetonitrile,33 p-xylene,72 toluene,72 isopentyl alcohol,72 tetrahydrothiophene dioxide,71 W^V-dimethylacetamide,20,68,71 tetrahydrofuran (THF),33 and tetramethylurea (TMU). 25 Pyridine may have been chosen originally for its good solvent properties but was later found to form a complex with copper (I) cyanide and this has occasionally been preformed and used as a reactant. 19 Suzuki and Hanafusa14 demonstrated that for the replacement of one or more iodine atoms, HMPT acts as an efficient solvent (which may also have other roles) and this has been confirmed by other workers,26,33 although it is not invariably the best solvent.25 However, in view of its suspected carcinogenic effect,73 it should be used with care (see also section II).…”
Section: B Choice Of Solventmentioning
confidence: 99%
“…Tetramethylurea gave better results than heating without solvent, or with HMPT or Me2SO for a 2,3-dibromonaphthalene. 25 The rate of a particular cyanation may vary according to the solvent used. For example, cyanation of the trifluoride (14) proceeded much more slowly and needed a higher temperature in diethylene glycol bis-(methyl ether) than in DMF.…”
Section: B Choice Of Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…14 This kind of reaction has been well studied 15 but there are only a few examples of syntheses which leave one out of several halogens unaltered. 16 Various cyanation procedures with KCN using organometallic catalysts have been described in the literature. 17 However, in our hands, any attempt to realise a monocyanation of the bisiodobenzylidene 3 with KCN and palladium catalyst (tetrakis(triphenylphosphine)palladium(0) or palladium acetate) led essentially to bisnitriles as major products in addition to unreacted bishalogen compounds.…”
Section: Chemistrymentioning
confidence: 99%
“…Tn unactivated systems cuprous cyanide was use d for the synthesis of nitriles at temperature s of 180-250°C and in the absence of solvent l -4 , while at lower temperatures basic solvents (pyridine s ,6, quinoline?) or dipolar solvents (N-methylpyrrolidone B ,9 , dimethyl sulfoxid e, tetram ethylurea 10) could be used. In some instances substitution took place more rapidly with sodium cuprous d icyanide l , NaCu( CN)2, or potassi um hexacyanod inickelate 12 , K4Ni 2( CN)6'…”
mentioning
confidence: 99%